Peran Pendidikan Pancasila dan Kewarganegaraan Bagi Masa Depan Bangsa - Fadillah, Nuzulul; Bowo, Ahmad Nasir Ari (Academy of Social Science and Global Citizenship Journal, 2021)
Pancasila and citizenship education are very important to be taught in the world of education at all levels of school. In addition to providing provisions to love the homeland,its application is also needed to give the spirit of nationalism to indonesian children. Pancasila education is the subject of current and future behavior. In this digital era,it is certain that the progress of the times and the challenges of globalization will greatly affect the lives of indonesian people. (Wahyunita et al., 2020). Therefore,in order to fortify attitudes that are not in accordance with the values contained in the points of Pancasila,in-dept teaching about future problems is needed. With this subject,it is hoped that later generations of the nation will be able to equip themselves with his love for the homeland and filtering various aspects that come from outside,especially those that are not in accordance with the personality of the Indonesian nation. The young generation is directed to take the existing positive values and reject all negative values that can destroy the nation. Pancasila education is also very important to be instilled in the younger generation in order to foster an attitude of national spirit and to be able to contribute in fulfilling the independence that has been achieved by those founding fathers of the nation who have given up their wealth and lives in order to achieve freedom from foreign nations.